Determinants of student interest in participating National Defense in the “Merdeka Belajar Kampus Merdeka” Program - Rahman Arifuddin; Subairi Subairi; Dwi Arman Prasetya; Wahyu Dirgantara (Jurnal Penelitian, 2021)
Merdeka Belajar Kampus Merdeka (MBKM) was established through Permendikbud No. 3 of 2020 concerning National Standards for Higher Education (SN-Dikti). MBKM brings significant changes, where universities must make adjustments to these changes. The success of the implementation of MBKM in higher education is measured using 8 Key Performance Indicators (IKU). One of the 9 BKP that is quite interesting is the National Defense activity or Komponen Cadangan (Komcad). Currently, the Ministry of Defense is preparing derivative regulations from the RI Law Number 23 of 2019 concerning the Management of National Resources for National Defense relating to the formation of Reserve Components. Discipline and Honesty. Student motivation directly influences Interest in Enrolling in the MBKM: Komcad Program, meaning that each student's motivation greatly encourages student interest in enrolling in the MBKM: Komcad program. Indirectly, discipline through Student Motivation has a significant influence on Interest in Enrolling in the MBKM: Komcad Program, meaning that Interest in Enrolling in the MBKM: Komcad Program is strongly influenced by the discipline and motivation of the students themselves.